A potassium chloride to glycine betaine osmoprotectant switch in the extreme halophile Halorhodospira halophila - Deole, Ratnakar (Sci Rep, 2020)
Halophiles utilize two distinct osmoprotection strategies. The accumulation of organic compatible solutes such as glycine betaine does not perturb the functioning of cytoplasmic components, but represents a large investment of energy and carbon. KCl is an energetically attractive alternative osmoprotectant, but requires genome-wide modifications to establish a highly acidic proteome. Most extreme halophiles are optimized for the use of one of these two strategies. Here we examine the extremely halophilic Proteobacterium Halorhodospira halophila and report that medium K(+) concentration dramatically alters its osmoprotectant use. When grown in hypersaline media containing substantial K(+) concentrations, H. halophila accumulates molar concentrations of KCl. However, at limiting K(+) concentrations the organism switches to glycine betaine as its major osmoprotectant. In contrast, the closely related organism Halorhodospira halochloris is limited to using compatible solutes. H. halophila performs both de novo synthesis and uptake of glycine betaine, matching the biosynthesis and transport systems encoded in its genome. The medium K(+) concentration (~10 mM) at which the KCl to glycine betaine osmoprotectant switch in H. halophila occurs is near the K(+) content of the lake from which it was isolated, supporting an ecological relevance of this osmoprotectant strategy.